Removal of caffeine, nicotine and amoxicillin from (waste)waters by various adsorbents. A review. (1st May 2020) - Anastopoulos, Ioannis; Pashalidis, Ioannis; Orfanos, Alexios G.; Manariotis, Ioannis D.; Tatarchuk, Tetiana; Sellaoui, Lotfi; Bonilla-Petriciolet, Adrián; Mittal, Alok; Núñez-Delgado, Avelino
Abstract: The fast growth in the anthropogenic activities, that involve a wide use of pharmaceuticals, has led to the appearance of new toxic and hazardous chemical compounds, called "emerging pollutants", which could cause unpredictable consequences to the ecosystems. The current review is focused on emerging pollutants occurring in food or air and include caffeine and nicotine, as well as on pharmaceuticals, in particular amoxicillin, and the concerns caused by its wide usage for medical purposes. This review, for the first time, analyzes and discusses the potential risks and implications of caffeine, nicotine and amoxicillin as emerging environmental pollutants, a field that remains underrepresented to date. Both caffeine and nicotine belong to life style compounds, while pharmaceutical amoxicillin is one of the very popular β-lactam antibiotics used to take care of human and animal infections. The review covers the toxic effect caused by caffeine, nicotine and amoxicillin on humans and animals and describes some of the main adsorbents utilized for their removal (e.g., grape stalk, tea waste, wheat grains, bentonite, activated carbon, acid and base modified grape slurry wastes, graphene oxides, modified graphene oxides, zeolites, etc.). The isotherm and kinetic models for the analysis of caffeine, nicotine and amoxicillin adsorption by different adsorbents are presented. The impact of pH, temperature, adsorbent dosage and thermodynamic studies were deeply analyzed. The review also discusses the mechanism of adsorption for the above-mentioned emerging pollutants, which includes π–π interaction, cation-π bonding, electron-donor and electron-acceptor forces, van der Waals forces, electrostatic interactions, etc. The present review has a potential value for chemists, ecologists, toxicologists, environmental engineers, and other professionals that are involved in environmental protection. Highlights: The removal of caffeine, nicotine, and amoxicillin from waters by various adsorbents is reviewed. The effect of physicochemical parameters on the adsorption efficiency is discussed in detail. Maximum adsorption capacities, and best fits of isotherm and kinetic models are compiled. Adsorption mechanisms are presented and discussed.